Optimisation of EMI shielding effectiveness: mechanical and physical performance of mortar containing POFA for plaster work using Taguchi Grey method - Narong, O.L.C.; Chee, Kiong Sia; See, Khee Yee; Pauline, Ong; Zainudin, Azlan; Muhd Nor, Nik Hisyamudin; Hassan, Mohd Fahrul (Elsevier Ltd, 2018)
A waste material which is collected from palm oil mill called POFA is used as cement replacement in plastering work to overcome electromagnetic interference issue. This study proposes Taguchi-Grey method to assess the optimal mixtures in plastering work with multiple responses of POFA. The responses under investigation are EMI shielding effectiveness, 28-days compressive strength, 28-days flexural strength, shrinkage, slump flow, initial setting time, final setting time, water retention and air content. In the application of this method, POFA admixture percentage, topcoat powder-to-binder ratio, water-to-binder ratio, latex agent content, particle size of POFA, and curing condition are selected as control factors. From the results it had been demonstrated and verified that the optimal mixture has 20% of POFA admixture, 0% of topcoat powder-to-binder ratio, 0.6 of water-to-binder ratio, 10% of latex agent content, 140 mm of POFA particle size and with water immersion curing condition are the optimal mixture. After comparison of the verification results, the Taguchi Grey method is applicable for this study due to the confirmation result which is comparable and fulfill the standard (IEEE Std 299-1997, BS EN 998-1, ASTM C1329, ASTM C596, and ASTM C1437) requirement.